AB0826 Development and Pilot Testing of An Online Gout Education Tool – Mygoutcare®. (15th July 2016) - Khanna, P.P.; Rankin, A.; An, L.; Khanna, D.
Abstract : Background: Recent management guidelines for gout have identified unmet educational needs in patients with gout. Qualitative studies have documented that there is a paucity of patient-focused materials to facilitate ongoing patient-physician communication. Objectives: To develop and test a web-based interactive educational resource for patients with gout tailored to improve their knowledge. This electronic platform has the potential to educate patients about gout and help facilitate communication with their physician to improve long term outcomes. Methods: The website was developed in four phases. 1. Two advisory panels - 30 gout patients and 10 gout experts iteratively reviewed pre-identified content areas of modifiable gaps in pathogenesis, natural history and treatment goals from previously conducted focus groups 1 . They evaluated the design (graphics and lay out) of the website and provided written input. 2. Incorporation of a validated knowledge questionnaire 2 on gout and a 5-minute post-survey to assess knowledge about critical take-home messages and satisfaction with their physician's care. 3. With a team of web designer and health informatics expert content areas were tailored in the website so the patient could walk through their own journey to learn various aspects of gout including triggers of flares, comorbidities, pharmacologic and non-pharmacologic treatment, healthy gout diet, and lifestyle choices. 4. Beta testing by patients with gout in clinics for clarity and usability. The website is called MyGoutCare® and in the pilot study, the patient completes a baseline survey of demographics and gout knowledge, reviews the website and generates a list of customized questions (Mygoutreport®) to discuss at the upcoming visit with their physician. They next complete a post-survey within two weeks of the physician visit. Data was analyzed using a paired t-test and presented as mean change in scores between post and baseline surveys. Results: 10 patients beta-tested the website for clarity, format, and flow. In the ongoing pilot study 22 subjects (mean age of 57 years, disease duration of 9.5 years, and 3–5 flares per year) were recruited from general medicine, podiatry, and rheumatology clinics and have completed MyGoutCare®. They were extremely receptive of an e-learning tool that was accessible 24/7. Pre-survey scores (0–10) on knowledge questions improved significantly (20%) when compared to post-survey scores with mean (SD) at -1.95 (1.76), p<0.001. All subjects reported satisfaction with the discussion on the natural history of disease and treatment choices. Most importantly they reported actionable changes moving forward, such as decision to continue lifelong urate-lowering therapy, compliance with monitoring serum urate, and dietary changes to achieve flare-free status. Conclusions: Our preliminary data suggests web-based patient-focused materials can serve as a practical tool to positively impact ongoing educational needs of patients in busy clinical practice. It remains to be seen if this will lead to better long term outcomes and improve patient-physician interactions. References: Khanna P. Gouty patients and clinicians admit to knowledge gaps about the disease: A qualitative experience from the US. Ann Rheum Dis. 2013;72(Suppl 3):768. Zhang LY et al. Development and evaluation of a survey of gout patients concerning their knowledge about gout. J Clin Rheumatol. 2011 Aug;17(5):242–8. Disclosure of Interest: P. Khanna Grant/research support from: research supported by investigator initiated grant to University of Michigan by AstraZeneca, A. Rankin: None declared, L. An: None declared, D. Khanna: None declared